A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 10 SIAK IN COMPREHENDING ENGLISH FABLES - Gultom, Effendy; Pravitasari, Dwi (SOROT, 2013)
Reading English text is very important because it gives usan opportunity to gain knowledge. In English learning, being able toread English text well is a necessity. Therefore, good ability in readingEnglish texts is very important for the students. Reading processinvolves the interaction between readers and the texts. In otherwords, reading is an activity which makes the readers’ minds active.In reading activities, the students need to understand not only theirtext books but also any kinds of printed media such as: magazines,newspaper, etc. However, the students often feel bored when theyread because the texts are too long and contain many difficult words.Therefore, they get difficulties to understand them. As a result, theirability in reading English texts is low.